2018
DOI: 10.1101/286005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retinal Ganglion Cell Axon Sorting at the Optic Chiasm Requires Dystroglycan

Abstract: Statement 1Abnormal retinal ganglion cell axon sorting in the optic chiasm in the absence of 2 functional dystroglycan results in profound defects in retinorecipient innervation. 3 4 Abstract 5In the developing visual system, retinal ganglion cell (RGC) axons project 6 from the retina to several distal retinorecipient regions in the brain. Several 7 molecules have been implicated in guiding RGC axons in vivo, but the role of 8 extracellular matrix molecules in this process remains poorly understood. 9Dystrogly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Axon sorting at the optic chiasm has been extensively studied in mice, where it is important, for example, for ipsilateral projection. Here, dystroglycan depletion resulted in chiasm axon sorting defects (Clements and Wright, 2018), while a similar observation was made for heparan sulfate proteoglycan in the zebrafish (Lee et al, 2004). Since these extracellular matrix molecules are known to bind Slits with high affinity, it has been suggested that the axon sorting alterations occur as a result of a disruption in the extracellular distribution of Slit2 (Wright et al, 2012).…”
Section: Discussionsupporting
confidence: 62%
“…Axon sorting at the optic chiasm has been extensively studied in mice, where it is important, for example, for ipsilateral projection. Here, dystroglycan depletion resulted in chiasm axon sorting defects (Clements and Wright, 2018), while a similar observation was made for heparan sulfate proteoglycan in the zebrafish (Lee et al, 2004). Since these extracellular matrix molecules are known to bind Slits with high affinity, it has been suggested that the axon sorting alterations occur as a result of a disruption in the extracellular distribution of Slit2 (Wright et al, 2012).…”
Section: Discussionsupporting
confidence: 62%
“…Intrinsic transcriptional codes not only differentiate ipsiRGCs from contraRGCs (2, 25), they also provide these ipsilateral projecting cells with a unique repertoire of cell surface receptors to respond uniquely to molecule cues as they course into the brain. Indeed, cell-cell and cell-ECM mechanisms drive the divergence of ipsiRGC axons at the optic chiasm and their homophilic fasciculation in the optic tract (51, 52, 54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…After mingling with each other in the optic chiasm, crossed and uncrossed fibers immediately segregate in the proximal optic tract (Sitko et al ., ). The molecular underpinnings of this segregation are beginning to emerge, and include dystroglycan (Clements & Wright, ), matrix molecules (Reese et al ., , ; Hornberg et al ., ), glial cells (Reese et al ., ; Lee et al ., ), and elements important for local translation of guidance proteins (Hornberg et al ., ), but a strict expression pattern associated with the ipsi‐ vs. contralateral RGC populations has not been established. Our in vitro analyses indicate that mouse ipsilateral RGCs have a greater propensity to fasciculate with their own ‘kind’ compared with contralateral RGCs (Sitko et al ., ).…”
Section: Development Of the Ipsilateral And Contralateral Projection mentioning
confidence: 99%